Predictive Value of Heart Rate and Blood Pressure on the Prognosis of Postural Tachycardia Syndrome in Children - Wang, Shuo; Zou, Runmei; Cai, Hong; Wang, Cheng (Frontiers in Pediatrics, 2022)
Background: To investigate the predictive value of heart rate (HR) and blood pressure (BP) on the prognosis of postural tachycardia syndrome in children (POTS). Materials and Methods: 53 cases of children aged 5 to 15 years who visited in the Pediatric Syncope Specialist Clinic of The Second Xiangya Hospital of Central South University for unexplained syncope or syncope precursor were diagnosed with POTS by head-up tilt test (HUTT) as POTS group. 38 healthy children aged 5 to 16 years who underwent physical examination at the Child Health Care Clinic of the hospital in the same period were matched as controls (Control group). The children with POTS were followed up after 3 months’ treatment, and were divided into good prognosis group (40 cases) and poor prognosis group (13 cases) according to the results of HUTT re-examination and whether the symptoms improved or not. HR and BP indicators were collected from each group at baseline and during HUTT. Results: There were 91 research subjects, 45 of the males, with a mean age of 11.28 ± 2.03 years. 1) HR at 5 min and 10 min (HR 5, HR 10), HR difference at 5 min and 10 min (HRD 5, HRD 10), HR and BP product at 5 min and 10 min (RPP 5, RPP 10) was greater in the POTS group than in the control group (P<0.01). 2) HR 5, HR 10, HRD 5, HRD 10 and RPP 10 in children with POTS were smaller in good prognosis group than poor prognosis group (P<0.01). 3) The area under curve was 0.923 on the four combined indicators (HR 5, HR 10, HRD 5, HRD 10) predicting a good prognosis of POTS, sensitivities and specificities of 99.99% and 75.00%, respectively. Conclusions: HR 5, HR 10, HRD 5, HRD 10, RPP 10 and the four combined indicators (HR 5, HR 10, HRD 5, HRD 10) had predictive value for the POTS’ prognosis in children. The predictive value of the four combined indicators for the POTS’ prognosis was better than that of the single HR 5, HRD 5 and RPP 10.